2012
DOI: 10.1257/aer.102.6.2674
|View full text |Cite
|
Sign up to set email alerts
|

Maturity, Indebtedness, and Default Risk

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
272
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(277 citation statements)
references
References 21 publications
5
272
0
Order By: Relevance
“…The set of amount of bonds is B D OEb min ; 1/ R where b min Ä 0. The lower bound is the highest level of debt that the country can hold-that is, b min < y max =r as in Arellano (2008) and Chatterjee and Eyigungor (2012). We assume that q.b tC1 ; h t ; y t / is the price of a bond with asset position (b tC1 ), credit record (h t ), and income level (y t ).…”
Section: Basic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The set of amount of bonds is B D OEb min ; 1/ R where b min Ä 0. The lower bound is the highest level of debt that the country can hold-that is, b min < y max =r as in Arellano (2008) and Chatterjee and Eyigungor (2012). We assume that q.b tC1 ; h t ; y t / is the price of a bond with asset position (b tC1 ), credit record (h t ), and income level (y t ).…”
Section: Basic Frameworkmentioning
confidence: 99%
“…We use a conventional debt restructuring model with one-period zero-coupon bonds as in Benjamin andWright (2009), Bi (2008), and Yue (2010). Some recent studies use models with long maturity bonds without restructurings, for instance Hatchondo and Martinez (2009), Chatterjee and Eyigungor (2012), and Arellano and Ramanarayanan (2012).…”
Section: Basic Frameworkmentioning
confidence: 99%
“…On runs and rollover risk in the sovereign debt context,Chatterjee and Eyigungor (2011).© 2013 The Author(s). The Economic Journal © 2013 Royal Economic Society.F22 T H E E C O N O M I C J O U R N A L [ F E B R U A R Y…”
mentioning
confidence: 99%
“…3 The international quantitative sovereign debt literature emphasizes instead incentives, lack of commitment, and the resulting default risk. Hatchondo, Carlos, and Martinez (2009) and Chatterjee and Eyigungor (2012) showed that restricting the government to issue long-term bonds improves the quantitative fit of sovereign debt models, and discussed the government's incentives to dilute existing bondholders. Arellano and Ramanarayanan (2012) introduced maturity choice into this framework and showed that a calibrated version of the model features shortening maturity as default risk increases.…”
Section: Related Literaturementioning
confidence: 99%